(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In recent times, the rapid growth in construction waste generation has raised significant environmental and economic concerns in recent times. However, Building Information Modelling (BIM) has emerged as a promising solution for managing construction waste and promoting sustainability. BIM offers advanced capabilities for visualization, simulation, and data-driven decision-making, making it a valuable tool for optimizing waste reduction strategies in construction projects. This paper offers a thorough and in-depth review that examines the present and prospective trends of BIM research and its implications in the realm of construction waste management (CWM). Through a Bibliometric analysis, a total of 637 publications were collected from the "Web of Science" core database. Employing VOSviewer for analysis and visualization, co-occurrence, co-word analysis, cluster analysis, and co-citation analyses were conducted to explore influential authors and journals, high-frequency keywords, recent research trends, and potential future research directions in the field. The findings shed light on crucial topics in BIM for CWM, such as circular economy, recycling, waste estimation, and waste reduction. The study systematically analyzes and categorizes the existing literature, mapping the knowledge landscape, and highlights the main future trends in academic research on the integration of BIM and CWM. Looking ahead, future research is anticipated to focus on integrating BIM with Internet of Things (IoT) models, incorporating circular economy BIM systems, exploring green building using BIM models, implementing BIM-based design for deconstruction, and adopting multi-dimensional BIM frameworks. This comprehensive review provides innovative insights into the unique contributions of BIM for CWM, differentiating it from prior research and enhancing the paper's scholarly impact.